Hibernation induction in non-hibernating species. (13th April 2018) - Pan, Mingke
Abstract: Hibernation is a natural process in many mammals to maximise survival during extreme environmental conditions. It is characterised by profound physiological changes such as reductions in metabolic rates and core body temperature for prolonged periods of time of up to 9 months. The ability of hibernating animals to recover from hibernation with no obvious signs of organ injury makes them excellent models for the clinical application of this natural protective mechanism, which has generated great interest in medical research. Recent studies have shed more light on the genetic and molecular basis of hibernation and several chemical compounds have been demonstrated to play significant roles in the regulation of hibernation, with an increasing focus on investigating their potential clinical applications in organ preservation and even development of cryonics techniques. In this review, I will present recent progress made in understanding the mechanism of hibernation and highlight evidence for hibernation induction in non-hibernating mammals using chemical compounds; finally, I will discuss the potential for combining genetic techniques to induce metabolic suppression for therapeutic purposes.